Highly efficient cyclotrimerization of isocyanates using N-heterocyclic olefins under bulk conditions. Issue 83 (2nd October 2019) - Li, Chengkai; Zhao, Wuchao; He, Jianghua; Zhang, Yuetao
Abstract : N-Heterocyclic olefins promoted highly efficient, organocatalytic cyclotrimerization of isocyanates into isocyanurates under bulk conditions. Abstract : With a catalyst loading as low as 0.005%, high to excellent yields of isocyanurates could be achieved from N-heterocyclic olefin mediated organocatalytic cyclotrimerization of a wide range of isocyanates under bulk conditions. Experimental details coupled with structural characterization of the key intermediates led to comprehensive mechanistic studies of cyclotrimerization.